Actinomycosis after allogeneic hematopoietic stem cell transplantation despite penicillin prophylaxis. Issue 4 (5th July 2016) - Barraco, F.; Labussière‐Wallet, H.; Valour, F.; Ducastelle‐Leprêtre, S.; Nicolini, F.‐E.; Thomas, X.; Ferry, T.; Dumitrescu, O.; Michallet, M.; Ader, F.; ,
Abstract: Actinomycosis is a rare chronic and multifaceted disease caused by Actinomyces species frequently mimicking malignancy or other chronic granulomatous lung diseases. We report 4 original presentations of actinomycosis arising under supposed penicillin prophylaxis in allogeneic stem cell transplantation recipients.